May Your Soul Rest in Peace’: Theological Tensions and Cultural Identity in African Christian Funeral Rhetoric - Mudau, Ndidzulafhi (African journal of religion, philosophy and culture, 2025)
Background Funeral rhetoric provides insight into deeply held ideas about death, the afterlife, and the ties between the living and the dying. In African cultures, the expression "May your soul rest in peace" has received universal acceptance across numerous religious communities, but its theological implications are unknown. Purpose and Aim This study examines the theological conflicts that arise when African Christians use funeral speeches based on traditional African cosmology while professing Christian eschatological ideas. The study investigates how such rhetorics cause tensions between indigenous worldviews and Christian teaching, ultimately influencing religious identity formation. Methodology Using literary theological research techniques and contextual-evaluative hermeneutics, this study compares African traditional religious perspectives with Christian theological positions on death and the afterlife. Primary and secondary texts from both traditions were studied using an inculturation assessment methodology to investigate cosmological assumptions, eschatological beliefs, and ceremonial roles. Theoretical Framework The study employs Magesa's inculturation principles and Ukpong's contextual hermeneutics as analytical lenses, offering techniques for determining theological compatibility between cultural rhetoric and Christian theology. Findings The analysis reveals a conflict between traditional African funeral rhetoric and basic Christian beliefs on death, resurrection, and the intermediate state. The phrase "May your soul rest in peace" contains cosmological assumptions about ancestor agency and continual contact between living and dead that differ from biblical eschatology, resulting in what theologians call "theological dissonance." Conclusion Rather than mindlessly inheriting rhetorics that undermine theological coherence in soteriology and eschatology, this study contributes to practical theology by providing contextually relevant alternatives that respect both Christian doctrine and African cultural sensitivity. The study enhances inculturation discourse by illustrating how seemingly innocent ceremonial language can undermine doctrinal purity. It also provides a reproducible methodology for analysing cultural practices in contextual theology.